2016
DOI: 10.1021/acs.jafc.6b03856
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds and Sesquiterpene Lactones Profile in Leaves of Nineteen Artichoke Cultivars

Abstract: Leaves of globe artichoke are food industry byproducts gaining interest due to their therapeutic and nutraceutical potential. The total phenolics, flavonoids, and flavonols content as well as radical scavenging capacity and reducing antioxidant power were determined in leaves of 19 artichoke cultivars. An untargeted analysis based on high-resolution mass spectrometry was then carried out to profile phenolic compounds and sesquiterpene lactones (STLs). The phenolic profile of leaf extracts from different cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 49 publications
6
52
1
Order By: Relevance
“…is part of the Compositae (Asteraceae) family; it was already used as a vegetable in ancient Egypt and has been cultivated in Southern Europe since the 15th century. In contrast to other Compositae, artichokes synthesize a limited number of STLs, mainly cynaropicrin, grosheimin, and its derivative 8‐deoxy‐11,13‐dihydroxygrosheimin, all components mostly present in the leaves . Accordingly, patients sensitized to artichoke do not always react to other extracts or plants from the same family .…”
Section: Discussionmentioning
confidence: 99%
“…is part of the Compositae (Asteraceae) family; it was already used as a vegetable in ancient Egypt and has been cultivated in Southern Europe since the 15th century. In contrast to other Compositae, artichokes synthesize a limited number of STLs, mainly cynaropicrin, grosheimin, and its derivative 8‐deoxy‐11,13‐dihydroxygrosheimin, all components mostly present in the leaves . Accordingly, patients sensitized to artichoke do not always react to other extracts or plants from the same family .…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of PCA in elucidating the effects of genetic materials and several pre and postharvest factors on productivity and especially on quality parameters of several horticultural crops has been documented in several greenhouse and open-field studies [9,20,45,52,53]. This was also the case in the current study, since the score plot of the PCA clearly divided the PB-treated and untreated plants along PC1 with biostimulant treatments concentrating most of the morphometric (yield and dry biomass) and physicochemical parameters (leaf dry matter, protein, total phenols and ascorbic acid as well as K, Ca and Mg contents ( Figure 5).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Monocaffeoylquinic acids, namely 1‐, 3‐, and 5‐ O ‐caffeoylquinic acids were described in leaves, stalks and capitula of wild cardoon, artichoke, and cultivated cardoon . Until now, 4‐ O ‐caffeoylquinic acid has only been identified in artichoke and wild cardoon, with a wide range of variation between accessions. Studies of cardoon heads have identified 5‐ O ‐caffeoylquinic acid as the main phenolic compound in aqueous and hydroalcoholic extracts (108 mg g −1 dw) with a relative abundance ranging between 18–36 % .…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Ferulic acid was detected in cis ( Z ) and trans ( E ) forms in leaves (328 mg kg −1 dw), heads (79 mg kg −1 dw), flowers (69 mg kg −1 dw), and stems (34 mg kg −1 dw) of cultivated cardoon. Three monocoumaroylquinic acids (3‐, 4‐ and 5‐ p ‐coumaroylquinic acids) were analyzed in artichoke leaves and only the 3‐ p ‐coumarouylquinic acid was detected in cardoon flowers (0.5 mg g −1 dw) …”
Section: Bioactive Compoundsmentioning
confidence: 99%
See 1 more Smart Citation